Optimasi Fe-S Pada Residu Leaching Emas dengan Flotasi Powder Lime dan Lime Milk - Suratinoyo, Zahna Allya Zulfa; Amalia, Yasmina; Probowati, Dyah (Fakultas Teknik UMSU, 2025)
Gold processing using the leaching method can produce large amounts of residue that often contain iron (Fe) and sulphur (S). This residue has the potential to become hazardous waste if not managed properly, as the sulphide content can cause acid mine drainage and environmental contamination. The Fe-S content has potential as an additive in the construction industry, such as in asphalt and concrete mixtures. One method that can be used to separate and reuse the Fe-S components from leaching residues is flotation. This study was conducted quantitatively through laboratory experiments. The reagents used in this study were PAX (Potassium Amyl Xanthate) as a collector, MIBC (Methyl Isobutyl Carbinol) as a frother, and CuSO₄ and lime as modifiers. The lime used was powder lime (lime powder) and lime milk (dissolved lime). The objective of this study was to determine the influence of powder lime and lime milk variables in the flotation process of gold leaching residues, as well as to determine the optimal use of lime in terms of economic efficiency. The results obtained from this study indicate that flotation using powdered lime is more economical, with a lime cost of Rp165.60 per kg of feed, yielding an Fe content of 38.9% and an S content of 49.1%. Furthermore, the Fe recovery rate was 77.5% and the S recovery rate was 80.1%.